Proximal caries lesion detection using the Canary Caries Detection System: an in vitro study. Issue 4 (27th May 2015) - Jan, Janja; Wan Bakar, Wan Zaripah; Mathews, Sapna M.; Okoye, Linda O.; Ehler, Benjamin R.; Louden, Christopher; Amaechi, Bennett T.
Abstract: Objective: This study investigated the accuracy of the Canary System (CS) to detect proximal caries lesions in vitro, and compared it with conventional methods: International Caries Detection and Assessment System (ICDAS) II and bitewing radiography (BW). Methods: Visible proximal surfaces of extracted human teeth were assessed by ICDAS‐II before setting them in five manikin mouth models. Then contacting proximal surfaces in mouth models were assessed by BW and CS. Histological validation with polarized‐light microscopy served as a gold standard. Pairwise comparisons were performed on area under the curve (AUC), sensitivity, and specificity of the three methods, and corrected using Bonferroni's method. Sensitivities and specificities were compared using a test of proportions and AUC values were compared using DeLong's method. Results: The CS presented significantly higher sensitivity (0.933) than ICDAS‐II (0.733, P  = 0.01) and BW (0.267, P  < 0.001), and ICDAS‐II higher sensitivity than BW ( P  < 0.001). There were no significant differences between their specificity values: 0.825 (CS), 0.65 (ICDAS‐II), and 0.875 (BW). The AUC of CS (0.862) was significantly higher than of ICDAS‐II (0.681, P  < 0.001) and BW (0.577, P  < 0.001). Conclusion: The CS demonstrated greater accuracy in detecting proximal lesions than ICDAS‐II and BW, although without significantly higher specificity.